The hydraulic lung - Prime, David (Cranfield University, 2004)
A Hydraulic Lung has been designed and constructed. The Hydraulic Lung can inhale through a Dry Powder Inhaler (DPI) with a pre-determined level of inspiratory effort, and the characteristics of the inhalation profile generated, such as the peak pressure drop, peak flow rate and the flow acceleration are determined by the resistivity of the inhaler. The Hydraulic Lung has been used to explore the relationship between the level of inspiratory effort, the DPI resistivity and the resultant profile characteristics. A simple empirical equation has been found to describe the peak pressure drop achieved for any given level of inspiratory effort and device resistivity. This equation can be adapted to provide the equivalent peak inspiratory flow rate. A second simple empirical equation was found to describe the flow acceleration rate achieved under defined conditions of inspiratory effort and device resistivity. A clinical study has been performed to generate equivalent human inhalation data. A comparison between the relationships derived from the Hydraulic Lung data and the human inhalation data has demonstrated the validity of the key equation for pressure drop as a tool for predicHng human inhalation characteristics. The equation for flow acceleration rate was found to underestimate the flow accelerations achieved by human volunteers, but with slight modification could be used for this purpose. Correlations were established between the findings from this study and the work of earlier researchers in this area, which was based on clinical data alone. The Hydraulic Lung was also used as a practical tool for the evaluation of DPI performance in-vitro, including the behaviour of devices with variable resistivity which cannot easily be assessed using either standard pumps or sophisticated apparatus such as the Electronic Lung.